Some economic characteristics of internet platforms - Peter Plavčan; Rastislav Funta (DANUBE: Law, Economics and Social Issues Review, 2020)
Various internet platforms have rapidly developed into central points of everyday life, for private individuals as well as for companies (often dominated by a single or a few companies). At the same time these internet platforms are advancing into more and more areas of business. This creates the risk of dependency, abuse of power, manipulation, concentration of power, centralization of data and information with corresponding effects on technological development, innovation, economy, society and politics. From an economic point of view, this article examines how the strong market positions of internet platforms arise and can be maintained. The dynamics of these technology and innovation-driven markets and the differences from conventional markets are also discussed. These internet markets have emerged from a series of innovations and are characterized by rapid technological development. Taking into account the economic peculiarities as well as knowledge from innovation and governance research, recommendations are drawn up on how these problems can be dealt with.
Keywords: 330; Internet Platforms; Innovations; Lock-in Effect; Technological Development